Implementasi Computational Thinking Unplugged dalam Pembelajaran Seni Tari di Sekolah Indonesia Luar Negeri Davao, Filipina - Rosarina Giyartini; Dwi Alia; Muhammad Rijal Wahid Muharram; Retno Uly Nevyanti (Jurnal Pemberdayaan Masyarakat, 2022)
This service is based on an analysis of situations and problems, that until now dance learning at SILN Davao, Philippines is still using the dance studio education pattern. The orientation is that students memorize certain dance movements with imitates the teacher, without being given space to creatively. This has an impact on the closure of various intelligences possessed by students. SILN Davao, also often appears at state events to present the face of Indonesia to the public, but this is hampered by the lack of variety in dance learning in schools, which makes Indonesia seem to have minimal traditional arts. To hack this, this community service seeks to implement the concept of dance learning by applying unplugged computational thinking. The goal is that dance learning is not just a matter of memorizing motion, but students can creative ideas in the form of dance according to their level of development. To achieve this, methods used are community situation analysis, problem identification, setting goals, problem solving plans, social approaches, implementing activities, and evaluating. The results of this implementation show that the concept of dance learning at SILN Davao, Philippines that applies computational thinking unplugged can be applied to other SILNs.